The Influence of Work Engagement and Organizational Commitment on Organizational Citizenship Behavior in Kendal City Hospitality Employees - Rifki, Prayuda; Firmansyah, Fitri (Indonesian Journal Publisher, 2025)
This study aims to determine and analyze the effect of work engagement and Organization commitment, on organizational citizenship behavior in Hotel X Purwokerto employees. The sample in this study were 130 hotel employees in Kendal City. Data collection techniques in this study used questionnaire methods, documentation studies, interviews and participatory observation. Data processing in this study using the SPSS version 26 for Windows program. The results of this study prove that the effect of work engagement on organizational citizenship behavior is 0.013 <0.05 and the t value is 2.508> 1.978. There is no effect of organizational commitment and organizational citizenship behavior of 0.127 < 0.05 and the value of t count 0.231 > 0.05 and the value of t count 1.202 < 1.978, then there is a simultaneous influence of work engagement and organizational commitment on organizational citizenship behavior is 0.008 < 0.05 and the value of f count 4.989 > f table 3.07.